Pengaruh Sistem E-Filling, Kesadaran Wajib Pajak dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak di KPP Pratama 1 Padang - Denny Novi Satria; Gustin Maina Putri (Jurnal Ilmiah Pendidikan Scholastic, 2021)
The purpose of this research is to provide empirical evidence of the effect of the e-filling system, taxpayer awareness and tax sanctions on taxpayer compliance. The population in this study were 100 respondents consisting of taxpayers registered at KPP Pratama Padang Satu. Purposive sampling technique is a sampling technique used in this study using the Slovin formula. The sample in this study were 100 respondents consisting of taxpayers registered at KPP Pratama Padang Satu. This type of research is quantitative research. Multiple linear regression analysis was used in this study. The results showed that the E-Feling system had no effect on taxpayer compliance at the Padang 1 Primary Tax Service Office, while taxpayer awareness and tax sanctions partially had an effect on Taxpayer Compliance at the Primary Tax Service Office Padang 1.